Model for the deep defect‐related emission bands between 1.4 and 2.4 eV in AlN. Issue 8 (19th January 2017) - Lamprecht, M.; Jmerik, V. N.; Collazo, R.; Sitar, Z.; Ivanov, S. V.; Thonke, K.
Abstract: We report on defect‐related photoluminescence bands in the range from 1.4 to 2.4 eV in aluminum nitride bulk crystals and layers. Using continuous photoluminescence, photoluminescence excitation, and time‐resolved photoluminescence spectroscopy, we assign these bands to donor–acceptor pair transitions between shallow donor states or related slightly deeper DX − states of silicon or oxygen donors, and three different types of deep acceptors. These three different acceptors are most likely a ( V Al − 2 ( O N )) complex, a ( V Al − O N ) complex, and an aluminum vacancy V Al, or different charge states of these.